Geopolitics of the horn of Africa - Radaković Milovan (Međunarodni Problemi, 2012)
At the beginning, author provides concretization of terms geopolitics and conflict and an explanation of geographical term Horn of Africa. In the following discussion, characterization and classification of the conflict between African countries is carried out. The work also comprises an analysis of geopolitical characteristics of the Horn of Africa and provides a brief synthesis of the countries in the region. Further, it explains the mutual relations and the nature of the conflict between Ethiopia and Eritrea, current military presence in the Horn of Africa and the importance of Bab-el-Mandeb strait. The author analyzes energy connection between Horn of Africa and the Middle East, regional and interregional impacts on the Horn of Africa countries and gives concluding remarks.